Lactobacilli as a Vector for Delivery of Nanobodies against Norovirus Infection - Yoshikazu Yuki; Fanglei Zuo; Shiho Kurokawa; Yohei Uchida; Shintaro Sato; Naomi Sakon; Lennart Hammarström; Hiroshi Kiyono; Harold Marcotte (MDPI AG, 2022)
Passive administration of neutralizing antibodies (Abs) is an attractive strategy for the control of gastrointestinal infections. However, an unanswered practical concern is the need to assure the stability of sufficient amounts of orally administered neutralizing Abs against intestinal pathogens (e.g., norovirus) in the harsh environment of the gastrointestinal tract. To this end, we expressed a single-domain Ab (VHH, nanobody) against norovirus on the cell surface of Lactobacillus, a natural and beneficial commensal component of the gut microbiome. First, we used intestinal epithelial cells generated from human induced pluripotent stem cells to confirm that VHH 1E4 showed neutralizing activity against GII.17 norovirus. We then expressed VHH 1E4 as a cell-wall-anchored form in Lactobacillus paracasei BL23. Flow cytometry confirmed the expression of VHH 1E4 on the surface of lactobacilli, and L. paracasei that expressed VHH 1E4 inhibited the replication of GII.17 norovirus in vitro. We then orally administered VHH 1E4-expressing L. paracasei BL23 to germ-free BALB/c mice and confirmed the presence of lactobacilli with neutralizing activity in the intestine for at least 10 days after administration. Thus, cell-wall-anchored VHH-displaying lactobacilli are attractive oral nanobody deliver vectors for passive immunization against norovirus infection.